Mitsos Bilalis, Το παρελθόν στο δίκτυο: Εικόνα, τεχνολογία και ιστορική κουλτούρα στη σύγχρονη Ελλάδα (1994–2005) [Online pasts: image, technology and historical culture in contemporary Greece, 1994–2005] - Sichani, Anna-Maria (Historein, 2020)
Review of Mitsos Bilalis, Το παρελθόν στο δίκτυο: Εικόνα, τεχνολογία και ιστορική κουλτούρα στη σύγχρονη Ελλάδα (1994–2005) [Online pasts: image, technology and historical culture in contemporary Greece, 1994–2005]. Athens: Historein; National Documentation Centre, 2015. 182 pp.